Effects of polypyrrole coated rebar on corrosion behavior of tunnel lining with the combination effect of sustained loading and pre-existing cracks when exposed to chlorides. (10th October 2019) - Hu, Xiongyu; He, Chuan; Feng, Kun; Liu, Sijing; Walton, Gabriel
Highlights: Investigated conditions of sustained loading, pre-existing damage and reinforcement coating. Presents the mechanical behavior of tunnel lining with cracks under accelerated corrosion. Reveals the resistance of polypyrrole-coated rebar against chloride-induced corrosion of linings. Abstract: This paper presents an experimental study on the mechanical behavior of a tunnel lining with pre-existing cracks that is subjected to accelerated corrosion. The surface strain, deflection, and load capacity of the concrete liner material were recorded, as well as the degree of rebar corrosion and the crack patterns that developed. The efficacy of the polypyrrole reinforcement coating in minimizing the effects of corrosion and the reinforcement effect on the physical properties of the concrete specimens were examined. The results show that both the pre-existing cracks and sustained loading have noticeable influence on the corrosion behavior of tunnel lining. The specimens with polypyrrole coating exhibited a delayed onset of reinforcement corrosion, less steel mass loss, smaller specimen surface strains and smaller transverse and longitudinal crack width.